Power Stabilization Of A Stand-Alone Solar System Using Perturb and Observe MPPT Algorithm - Kamarudin, Muhammad Nizam; Jamri , Mohd Saifuzam (2010)
Solar energy is gaining more popularity for the choice of electricity generation as it is available everywhere especially in Malaysia and it is free to harness. This paper presents the method of power stabilization of a stand-alone solar system using perturb and observe (P&O) maximum power point algorithm. The PV module is modeled based on the parameters obtained from a commercial PV data sheet. A DC-DC boost converter is chosen to step up the input DC voltage of the PV module while the perturb and observe maximum power point algorithm is used and modeled to ensure the power stabilization is made. The model is simulated under a constant of solar irradiance and temperature in which follow the standard test condition (STC). The comparison between including and excluding of MPPT controller is also made and results show that the model yields the different performance.